Developing structural specification: Productivity in early Hebrew verb usage. Issue 1 (February 2013) - Lustigman, Lyle
The study investigates acquisition of verb inflections by four monolingual Hebrew-acquiring children from middle-class backgrounds, audio-recorded in longitudinal, weekly samples at a mean age-range of between 18 and 26 months. Productive use of inflectional morphology is shown to manifest increasing structural specification, as a function of children's developing knowledge of morphology–syntax interfaces illustrated by Subject–Verb agreement. The verbs used by all four children evolve from non-specified stem-like forms via sporadic structural alternations to initial productivity in the use of largely under-specified inflected forms. This process of increasing structural specification is interpreted as reflecting paradigmatic/syntagmatic interfacings in developing grammatical productivity, such that eventually a full range of inflectional contrasts is manifested in all and only appropriate syntactic environments.